Earliest fossil record of pollen-foraging megachiline bees - Christian Geier; Michael S. Engel; André Nel; Johannes M. Bouchal; Silvia Ulrich; Gabrielle Gourdet; Valérie Ngô Muller; Friðgeir Grímsson (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Palaeoecological potential of chironomid (non-biting midge) remains encountered on pollen slides - S. Engels; O. Heiri; J. Hinkelman; M. Jambrović (Review of Palaeobotany and Palynology, 2026)

Corrigendum to “Environmental exposure and cancer incidence in offshore petroleum workers in Norway” [Environ. Res. 264 (2025) 121407] - Ronnie Babigumira; Marit B. Veierød; Inger K. Larsen; Leon A.M. Berge; Nita K. Shala; Niki Marjerrison; Sven O. Samuelsen; Magne Bråtveit; Jorunn Kirkeleit; Karl-Christian Nordby; H Dean Hosgood; Paul A. Demers; et al. (Environmental Research, 2026)

GollumFit: An icecube open-source framework for binned-likelihood neutrino telescope analyses - R. Abbasi; M. Ackermann; J. Adams; S.K. Agarwalla; J.A. Aguilar; M. Ahlers; J.M. Alameddine; N.M. Amin; K. Andeen; C. Argüelles; Y. Ashida; S. Athanasiadou; et al. (Computer Physics Communications, 2026)

Longer-term neurological and endocrine/metabolic conditions in the deepwater horizon oil spill coast guard cohort study: A principal component analysis - Hristina Denic-Roberts; Jordan McAdam; Lawrence S. Engel; Jeanine M. Buchanich; Rachel G. Miller; Evelyn O. Talbott; Dana L. Thomas; Glen A. Cook; Blake Hansen; Jill E. Emerick; Tina Costacou; Jennifer A. Rusiecki (International Archives of Occupational and Environmental Health, 2026)
Purpose Deepwater Horizon oil spill (DWHOS) responders potentially experienced multiple stressors. We examined associations between DWHOS deployment-related stressor patterns and neurological and endocrine/metabolic conditions among U.S. Coast Guard active duty responders who completed post-deployment surveys (n = 3102). Methods Deployment-related stressor patterns were identified using principal component analysis of self-reported stressors. Neurological and endocrine/metabolic outcomes were classified from military health encounter records. Associations between principal components (PCs) and incident outcomes (2010–2015) were estimated through Cox proportional hazards regression. Results A five-component solution explained 79.2% of the variance. PC1 (high physical/moderate chemical stressor pattern) was associated with migraine [adjusted hazard ratio (aHR): 1.25, 95% confidence interval (CI): 1.01–1.56]. PC2 (high crude oil/dispersant stressor pattern) was associated with several migraine/headache conditions including migraine with aura (1.54, 1.14–2.07), mononeuritis of upper limb and mononeuritis multiplex (1.36, 1.11–1.68), disorders of lipid metabolism (1.11, 1.01–1.23 ) and its subcategory other and unspecified hyperlipidemia (1.11, 1.01–1.24), and dysmetabolic syndrome X (1.74, 1.19–2.54). PC3 (high fatigue/moderate chemical inhalation stressor pattern) was associated with several migraine/headache conditions (aHR range: 1.18–1.60), disorders of lipid metabolism (1.11, 1.00–1.23) including other and unspecified hyperlipidemia (1.13, 1.01–1.26) , and overweight and obesity (1.13, 1.00–1.27). PC4 (high anxiety/modest fatigue stressor pattern) was associated with abnormality of gait (1.34, 1.03–1.73). PC5 (high back pain) was associated with mononeuritis of lower limb, several balance and gait-related conditions , thyroid disorders, and obesity (aHRs range: 1.16–1.67). Conclusion Oil spill response stressor patterns were associated with increased risks of multiple longer-term neurological and endocrine/metabolic conditions, with associations varying by PC.

Corrigendum to ‘The environmental neuroactive chemicals list of prioritized substances for human biomonitoring and neurotoxicity testing: A database and high-throughput toxicokinetics approach’ [Environ. Res. 2025 (266) 120537] - Julia E. Rager; Lauren E. Koval; Elise Hickman; Caroline Ring; Taylor Teitelbaum; Todd Cohen; Giulia Fragola; Mark J. Zylka; Lawrence S. Engel; Kun Lu; Stephanie M. Engel (Environmental Research, 2026)

Associations between ambient exposure to styrene, benzene, toluene, ethylbenzene, and xylenes and hospitalizations in the US Gulf region - Yongsoo Choi; Chi-Tsan Wang; Joshua L. Warren; Jung-Hun Woo; Lawrence S. Engel; Bok Haeng Baek; Michelle L. Bell (Environmental Research, 2026)

Inter- and intra-specific trophic niche partitioning, and cryptic speciation in three deep-sea predators in the Indian Ocean - Baptiste Le Bourg; Jeremy J. Kiszka; Jérôme Spitz; Toby S. Daly-Engel; Paco Bustamante (Deep Sea Research Part I: Oceanographic Research Papers, 2026)

The first club-tailed dragonfly (Odonata: Gomphidae) in the Eocene Grube Messel (Germany) - Torsten Wappler; André Nel; Michael S. Engel (PalZ, 2026)

Cancer Risk and Mortality Following Kaposi Sarcoma Among People with HIV in the United States, 2000 to 2019 - Sally Peprah; Eric A. Engels; Qianlai Luo; Analise Monterosso; Colby H. Cohen; Ruth M. Pfeiffer; Meredith S. Shiels (Cancer Causes & Control, 2026)
People with HIV (PWH) have increased Kaposi sarcoma (KS) risk. Among 2,645 PWH with KS in the United States HIV/AIDS Cancer Match Study, subsequent cancer risk was elevated 2.8-fold (95% confidence interval [CI]: 2.4–3.3) compared to PWH without KS. Mortality after KS declined 2000–2002 and 2012–2015 (hazard ratio = 0.64; 95%CI: 0.55–0.74).

Associations between exposure to metals, chlorinated pesticides, and PCBs and differential leukocyte profiles in Flemish adolescents - Fen Zhang; Lützen Portengen; Hamid Y. Hassen; Laura Rodriguez Martin; Madeline Carsique; Amélie Crépet; Jasper Engel; Jacob Van Klaveren; Nicolas Van Larebeke; Willy Baeyens; Stefaan De Henauw; Tim S. Nawrot; et al. (Environmental Research, 2026)

A new genus of aphids from the Bqaatouta outcrop of Lower Cretaceous Lebanese amber (Hemiptera: Tajmyraphidoidea) - Michael S. Engel; Mounir Maalouf; André Nel; Dany Azar (Palaeoworld, 2025)

A new family of proctotrupomorphan wasps in Lower Cretaceous amber of Lebanon (Hymenoptera) - Michael S. Engel (Palaeoworld, 2025)

New ceraphronoid wasps in Cretaceous and Cenozoic ambers from Lebanon, New Jersey, and India (Hymenoptera: Ceraphronoidea) - Michael S. Engel (Palaeoworld, 2025)

First insights into the fine-scale vertical movements of a Carolina hammerhead, Sphyrna gilberti, and a hybrid between Carolina and scalloped hammerhead - Lauren Horstmyer; Kirsty Ballard; Toby Daly-Engel; Kieran Stein; Eric Hoffmayer; Neil Hammerschlag; Bryan S. Frazier; Brooke Anderson; Beckah Campbell; James Sulikowski (Frontiers in Marine Science, 2025)
Satellite telemetry has enabled the tracking of marine predators’ vertical and horizontal habitat use and migration patterns. These insights provide valuable information that inform management and conservation of threatened species. In this study, a scalloped hammerhead, Sphyrna lewini, (125 cm FL; immature female) a Carolina hammerhead, Sphyrna gilberti, (138 cm FL; immature female) and a scalloped/Carolina hammerhead hybrid (160 cm FL; immature male) were tagged with PSATLIFE’s off the coast of North Carolina. Tag data revealed that the Carolina hammerhead exploited a wide depth range, with a maximum depth of 846 m. Dive patterns of the scalloped hammerhead revealed differences in vertical space use, with the scalloped hammerhead primarily remaining within the top 200 m of the water column, and with a maximum depth of 380 m. The hybrid individual demonstrated similar dive patterns to those of the scalloped hammerhead, with a maximum depth of 203 m. This study presents the first vertical movement data for Carolina and hybrid scalloped/Carolina hammerheads, offering new insights into interspecific variation in depth use. Future research should explore if there are differences in habitat use and foraging strategies, as they may serve as distinguishing characteristics and support the development of effective management measures.

Marine protected areas miss key habitats of Bryde's whales and bottlenose dolphins exposed to anthropogenic stressors - Guilherme Maricato; Rodrigo Tardin; Clinton N. Jenkins; Fábio G. Daura-Jorge; Márcia H. Engel; Liliane Lodi; Israel Maciel; Milton C.C. Marcondes; Gabriel Melo-Santos; Lucas Milmann; Maria Alice S. Alves (Marine Pollution Bulletin, 2025)

Blood concentrations of volatile organic compounds and hypertension in the GuLF Study - Faye Koenigsmark; Kaitlyn G. Lawrence; Richard K. Kwok; Kate Christenbury; Dale P. Sandler; Lawrence S. Engel (Science of The Total Environment, 2025)

Associations between airborne crude oil chemicals and neurological symptoms among workers in the gulf long-term follow-up study - Kristen N. Cowan; Emily J. Werder; Kaitlyn G. Lawrence; Richard K. Kwok; Patricia A. Stewart; Mark R. Stenzel; Caroline P. Groth; Tran B. Huynh; Sudipto Banerjee; Gurumurthy Ramachandran; W. Braxton Jackson; Frankie LaPorte; et al. (Science of The Total Environment, 2025)

Association of oil spill cleanup-related hydrocarbon exposure with hypertension and blood pressure in the Gulf Long-term Follow-up Study - Opal P. Patel; Jessie K. Edwards; Anna M. Kucharska-Newton; Eric A. Whitsel; W. Braxton Jackson; Kaitlyn G. Lawrence; Patricia A. Stewart; Mark R. Stenzel; Lawrence S. Engel; Dale P. Sandler (Science of The Total Environment, 2025)

How long is long-term? Comparing decadal- and centennial-scale insect diversity dynamics - Stefan Engels; Christine S. Lane; Eloise Wilkinson-Rowe (Hydrobiologia, 2025)

Oil spill cleanup related exposures to benzene, toluene, ethylbenzene, xylenes, and n-hexane and incident diabetes mellitus - Hanna V. Jardel; Alexander P. Keil; Chantel L. Martin; David B. Richardson; Mark R. Stenzel; Patricia A. Stewart; Kate E. Christenbury; Lawrence S. Engel; Dale P. Sandler (Environmental Research, 2025)

Benzene exposure and risk of colorectal cancer by anatomical subsite in the Norwegian offshore petroleum workers cohort - Ronnie Babigumira; Marit B. Veierød; Inger K. Larsen; Leon A.M. Berge; Nita K. Shala; Niki Marjerrison; Sven O. Samuelsen; Magne Bråtveit; Jorunn Kirkeleit; Karl-Christian Nordby; H Dean Hosgood; Paul A. Demers; et al. (Environmental Research, 2025)

Unraveling the insect head: Segmentation and pancrustacean homologies - Patricia Nel; Michael S. Engel; Carmen Soriano; Sylvain Pont; Lauriane Jacquelin; Laurence Dollinger; Laure Desutter-Grandcolas; Tony Robillard; Romain Garrouste; Dany Azar; André Nel (Arthropod Structure & Development, 2025)

Environmental exposure assessment in the international prospective study of Chronic Kidney Disease of UnceRtain Etiology (CKDu) in Agricultural Communities (CURE) research consortium: Design and protocol development - Marvin González-Quiroz; Anna Aceituno; Shuchi Anand; Alexander van Geen; Lawrence S. Engel; Emmanuel Jarquin; Clemens Ruepert; Nicole Villegas-González; Mariela Arias-Hidalgo; Nora Franceschini; Daylin Anchía-Pastrán; Karla Solano-Diaz; et al. (Science of The Total Environment, 2025)

Organic Geochemistry and Paleodepositional environment of the Mushorah Formation in Sufaya and Ain Zala oilfields, Northwestern Iraq - Mohamed W. Alkhafaji; Mohamed R. M. Ahmed; Taher Mahmood Taha; Anwaar S. Al-Maadhidi; Jacques Connan; Michael H. Engel (Carbonates and Evaporites, 2025)

Prevalence of cardiovascular disease risk factors associated with residential natural hazard risk - Kaitlyn G. Lawrence; Marina R. Sweeney; Emily J. Werder; Casey Zuzak; Melanie Gall; Christopher T. Emrich; Ian D. Buller; W. Braxton Jackson; Dazhe Chen; Kate E. Christenbury; Lawrence S. Engel; Dale P. Sandler (Science of The Total Environment, 2025)

Stingless bee honey: Nutraceutical properties and urgent call for proposed global standards - Patricia Vit; Bajaree Chuttong; Elia Ramírez-Arriaga; Eunice Enríquez; Zhengwei Wang; Cleofas Cervancia; Favio Vossler; Sammy Kimoloi; Michael S. Engel; Ricardo R. Contreras; Christopher A. Mduda; Francisco Tomás-Barberán (Trends in Food Science & Technology, 2025)

GRANDlib: A simulation pipeline for the Giant Radio Array for Neutrino Detection (GRAND) - R. Alves Batista; A. Benoit-Lévy; T. Bister; M. Bohacova; M. Bustamante; W. Carvalho; Y. Chen; L. Cheng; S. Chiche; J.M. Colley; P. Correa; N. Cucu Laurenciu; et al. (Computer Physics Communications, 2025)

The environmental neuroactive chemicals list of prioritized substances for human biomonitoring and neurotoxicity testing: A database and high-throughput toxicokinetics approach - Julia E. Rager; Lauren E. Koval; Elise Hickman; Caroline Ring; Taylor Teitelbaum; Todd Cohen; Giulia Fragola; Mark J. Zylka; Lawrence S. Engel; Kun Lu; Stephanie M. Engel (Environmental Research, 2025)

A new labiduroid earwig from mid-Cretaceous Kachin amber (Dermaptera: Labiduroidea) - Ancheng Peng; Michael S. Engel; De Zhuo; André Nel (Cretaceous Research, 2025)

Impact of genetic polymorphisms on associations between crude oil exposure and health effects among Coast Guard Deepwater Horizon responders - Joseph B. Kim; Hristina Denic-Roberts; Jordan McAdam; Dana L. Thomas; Lawrence S. Engel; Jennifer A. Rusiecki (Science of The Total Environment, 2024)

The earliest large carpenter bee (Xylocopa) and its adhering pollen (Araliaceae, Theaceae) - Christian Geier; Michael S. Engel; Johannes M. Bouchal; Silvia Ulrich; Friðgeir Grímsson; Sonja Wedmann; Torsten Wappler (Palaeobiodiversity and Palaeoenvironments, 2024)
The association of pollinators with their host plants is a critical element of ecosystem functioning and one that is usually determined indirectly in the fossil record from specific morphological traits of flowers or putative pollinating animals. The exceptionally fine preservation at Messel, Germany, offers an excellent source of data on pollen from fossil flowers as well as preserved adhering to insects as direct evidence of their association with specific floral lineages. Here, we report on pollen recovered from the body and legs of a large carpenter bee (Apidae: Xylocopinae: Xylocopini) from the Eocene of Messel. The fossil is the earliest occurrence of the tribe Xylocopini and represents an extinct subgenus and species, described as Xylocopa ( Apocolyx ) primigenia subgen. et sp. nov. Two eudicot pollen types were recovered from the bee, one of the family Theaceae (Asterids: Ericales) and another of Araliaceae (Euasterids: Apiales). The pollen grains are compared with various extinct and extant pollen types, and data on floral visitors to modern theaceous and araliaceous flowers are explored in relation to understanding the association of the fossil carpenter with these floral types in the paratropical Eocene biota of Messel.

A review of the solitary wasp genus Apodynerus from Vietnam (Hymenoptera: Vespidae) - Lien Thi Phuong Nguyen; Ngat Thi Tran; Anh Duc Nguyen; Michael S. Engel (Zoologischer Anzeiger, 2024)

Estimating rates of change to interpret quantitative wastewater surveillance of disease trends - David A. Holcomb; Ariel Christensen; Kelly Hoffman; Allison Lee; A. Denene Blackwood; Thomas Clerkin; Javier Gallard-Góngora; Angela Harris; Nadine Kotlarz; Helena Mitasova; Stacie Reckling; Francis L. de los Reyes; et al. (Science of The Total Environment, 2024)

Residential Proximity to Metal-Emitting Industries and Toenail Metal Concentration in the US Gulf States - Joyce J. Y. Lin; Emily J. Werder; Kaitlyn G. Lawrence; W. Braxton Jackson; Dale P. Sandler; Aisha S. Dickerson; Lawrence S. Engel; Ana M. Rule (Exposure and Health, 2024)

A Systematic Review of Anthropogenic Noise Impact on Avian Species - Margret S. Engel; Robert J. Young; William J. Davies; David Waddington; Michael D. Wood (Current Pollution Reports, 2024)
Purpose of review This study aims to investigate anthropogenic noise impact on avian species by means of a systematic review of literature. Recent findings Based on previous anthropogenic noise impact frameworks, it was possible to: clarify the impacts of noise on birds; optimise the existing frameworks with findings produced over 44 years; recategorise noise impacts into more appropriate categories, indicating which are the positive and negatives, as well as acute and chronic impacts caused by anthropogenic noise; provide a significant cluster model of anthropogenic noise impacts on avian species subdivided into impacts on ‘Behaviour’ and ‘Communication/Perception’ (Cluster 1) and ‘Physiology’ (Cluster 2); and show how avian hearing frequency range overlaps noise source frequency range. Summary This research adopted the database of Peacock et al. [1, 2] regarding avian species due to its vast coverage across taxa. A systematic literature review of 50 peer-reviewed papers about anthropogenic noise impact on birds was undertaken. A Two-Step Cluster analysis was calculated, showing the data subdivided into two clusters. Cluster 1 (76.9%) showed behavioural responses mainly composed of negative and auditory perception and communication impacts, presenting positive or negative noise impacts. Cluster 2 (23.1%) mainly showed negative impacts on physiological outcomes caused by traffic, anthropogenic, and background noise.

Comparative analysis of 12 water lily plastid genomes reveals genomic divergence and evolutionary relationships in early flowering plants - Weicai Song; Wenbo Shi; Huan Wang; Zirui Zhang; Ruiqing Tao; Jin Liu; Shuo Wang; Michael S. Engel; Chao Shi (Marine Life Science & Technology, 2024)
The aquatic plant Nymphaea , a model genus of the early flowering plant lineage Nymphaeales and family Nymphaeaceae, has been extensively studied. However, the availability of chloroplast genome data for this genus is incomplete, and phylogenetic relationships within the order Nymphaeales remain controversial. In this study, 12 chloroplast genomes of Nymphaea were assembled and analyzed for the first time. These genomes were 158,290–160,042 bp in size and contained 113 non-repeat genes, including 79 protein-coding genes, 30 tRNA genes, and four rRNA genes. We also report on codon usage, RNA editing sites, microsatellite structures, and new repetitive sequences in this genus. Comparative genomics revealed that expansion and contraction of IR regions can lead to changes in the gene numbers. Additionally, it was observed that the highly variable regions of the chloroplast genome were mainly located in intergenic regions. Furthermore, the phylogenetic tree showed the order Nymphaeales was divided into three families, and the genus Nymphaea can be divided into five (or three) subgenera, with the subgenus Nymphaea being the oldest. The divergence times of nymphaealean taxa were analyzed, with origins of the order Nymphaeales and family Nymphaeaceae being about 194 and 131 million years, respectively. The results of the phylogenetic analysis and estimated divergence times will be useful for future evolutionary studies of basal angiosperm lineages.

Associations of a toenail metal mixture with attention and memory in the Gulf long-term follow-up (GuLF) study - Joyce J.Y. Lin; Jordan R. Kuiper; Aisha S. Dickerson; Jessie P. Buckley; Heather E. Volk; Diane S. Rohlman; Kaitlyn G. Lawrence; W. Braxton Jackson; Dale P. Sandler; Lawrence S. Engel; Ana M. Rule (Science of The Total Environment, 2024)

Geography and ecology shape the phylogenetic composition of Amazonian tree communities - Bruno Garcia Luize; David Bauman; Hans ter Steege; Clarisse Palma‐Silva; Iêda Leão do Amaral; Luiz de Souza Coelho; Francisca Dionízia de Almeida Matos; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Florian Wittmann; Carolina V. Castilho; Marcelo de Jesus Veiga Carim; et al. (Journal of Biogeography, 2024)
Aim Amazonia hosts more tree species from numerous evolutionary lineages, both young and ancient, than any other biogeographic region. Previous studies have shown that tree lineages colonized multiple edaphic environments and dispersed widely across Amazonia, leading to a hypothesis, which we test, that lineages should not be strongly associated with either geographic regions or edaphic forest types. Location Amazonia. Taxon Angiosperms (Magnoliids; Monocots; Eudicots). Methods Data for the abundance of 5082 tree species in 1989 plots were combined with a mega‐phylogeny. We applied evolutionary ordination to assess how phylogenetic composition varies across Amazonia. We used variation partitioning and Moran's eigenvector maps (MEM) to test and quantify the separate and joint contributions of spatial and environmental variables to explain the phylogenetic composition of plots. We tested the indicator value of lineages for geographic regions and edaphic forest types and mapped associations onto the phylogeny. Results In the terra firme and várzea forest types, the phylogenetic composition varies by geographic region, but the igapó and white‐sand forest types retain a unique evolutionary signature regardless of region. Overall, we find that soil chemistry, climate and topography explain 24% of the variation in phylogenetic composition, with 79% of that variation being spatially structured ( R 2 = 19% overall for combined spatial/environmental effects). The phylogenetic composition also shows substantial spatial patterns not related to the environmental variables we quantified ( R 2 = 28%). A greater number of lineages were significant indicators of geographic regions than forest types. Main Conclusion Numerous tree lineages, including some ancient ones (>66 Ma), show strong associations with geographic regions and edaphic forest types of Amazonia. This shows that specialization in specific edaphic environments has played a long‐standing role in the evolutionary assembly of Amazonian forests. Furthermore, many lineages, even those that have dispersed across Amazonia, dominate within a specific region, likely because of phylogenetically conserved niches for environmental conditions that are prevalent within regions.

Cretaceous beetles of the Jinju Formation (Coleoptera): An overview of the Jinju Formation, its coleopteran diversity, and past and future research - Soo Bin Lee; Yan-Da Li; Chenyang Cai; Michael S. Engel; Gi Soo Nam; Jong Kyun Park; André Nel; Josh Jenkins Shaw; Corentin Jouault; Andrei Legalov; Robin Kundrata (Journal of Asia-Pacific Entomology, 2024)

Defining Mechanistic Pathways for Anthropogenic Noise Impact on Avian Species - Margret S. Engel; Robert J. Young; William J. Davies; David Waddington; Michael D. Wood (Current Pollution Reports, 2024)
Purpose of Review This review collates and analyses data on noise exposure of birds in relation to avian hearing system performance. It provides new insights into the mechanistic pathways of anthropogenic noise impact on avian species. Recent Findings Noise impacts both humans and wildlife. Birds are of conservation concern, given the recent reports of major global declines in bird populations and that one in eight bird species is threatened with extinction. Studies of noise impacts on birds have been, and continue to be, published. Whilst many of these studies report associations between noise and a response in birds, relatively few provide clear demonstration of the mechanisms of impact. Summary Anatomical and physiological datasets were compiled for species representing nineteen avian orders. Information on noise sources, propagation path and habitat selection was also collated. Bird order was not a good predictor of bird hearing frequencies, but body dimensions were. In general, smaller birds were found to have higher peak hearing frequencies than larger birds. Cranium height was the strongest predictor of peak hearing frequency for birds. These findings provide mechanistic context to noise impacts on birds and a potential basis for predicting responses of avian species to different noise environments.

Biodiversity responses to Lateglacial climate change in the subdecadally-resolved record of Lake Hämelsee (Germany) - S. Engels; C.S. Lane; W.Z. Hoek; I. Baneschi; A. Bouwman; E. Brogan; C. Bronk Ramsey; J. Collins; R. de Bruijn; A. Haliuc; O. Heiri; K. Hubay; et al. (Quaternary Science Reviews, 2024)

Defensive glands in Stylotermitidae (Blattodea, Isoptera) - Himanshu Thakur; Surbhi Agarwal; Aleš Buček; Jaromír Hradecký; Hana Sehadová; Vartika Mathur; Ulugbek Togaev; Thomas van de Kamp; Elias Hamann; Ren-Han Liu; Kuldeep S. Verma; Hou-Feng Li; et al. (Arthropod Structure & Development, 2024)

High-altitude characterization of the Hunga pressure wave with cosmic rays by the HAWC observatory - Ruben Alfaro; César Alvarez; Juan Carlos Arteaga-Velázquez; Arun Babu Kollamparambil Paul; Daniel Avila Rojas; Hugo Alberto Ayala Solares; Rishi Babu; Ernesto Belmont-Moreno; Chad Brisbois; Karen S. Caballero-Mora; Tomás Capistrán; Alberto Carramiñana; et al. (Advances in Space Research, 2024)

A new fossil fern of the Dryopteridaceae (Polypodiales) from the mid-Cretaceous Kachin amber - Xiaoxuan Long; Yuan Peng; Qi Feng; Michael S. Engel; Chao Shi; Shuo Wang (Palaeobiodiversity and Palaeoenvironments, 2023)

A call to termitologists: it is time to abandon the use of “lower” and “higher” termites - T. F. Carrijo; M. S. Engel; T. Chouvenc; G. H. Gile; A. Mikaelyan; F. Dedeine; J. L. Ware; I. Haifig; A. Arab; J. P. Constantini; J. P. Souza; S. -B. Lee; et al. (Insectes Sociaux, 2023)

Insect pollination in deep time - Constanza Peña-Kairath; Xavier Delclòs; Sergio Álvarez-Parra; Enrique Peñalver; Michael S. Engel; Jeff Ollerton; David Peris (Trends in Ecology & Evolution, 2023)

Isotopic and chemical signatures of high mountain rivers in catchments with contrasting glacier and rock glacier cover - S. Brighenti; M. Engel; R. Dinale; W. Tirler; G. Voto; F. Comiti (Journal of Hydrology, 2023)

Exposure to volatile hydrocarbons and neurologic function among oil spill workers up to 6 years after the Deepwater Horizon disaster - Dazhe Chen; Emily J. Werder; Patricia A. Stewart; Mark R. Stenzel; Fredric E. Gerr; Kaitlyn G. Lawrence; Caroline P. Groth; Tran B. Huynh; Gurumurthy Ramachandran; Sudipto Banerjee; W. Braxton Jackson II; Kate Christenbury; et al. (Environmental Research, 2023)

Structure and composition of natural ferrihydrite nano-colloids in anoxic groundwater - Maya Engel; Vincent Noël; Samuel Pierce; Libor Kovarik; Ravi K. Kukkadapu; Juan S. Lezama Pacheco; Odeta Qafoku; J. Ray Runyon; Jon Chorover; Weijiang Zhou; John Cliff; Kristin Boye; et al. (Water Research, 2023)

Traits of dominant plant species drive normalized difference vegetation index in grasslands globally - Thore Engel; Helge Bruelheide; Daniela Hoss; Francesco M. Sabatini; Jan Altman; Mohammed A. S. Arfin‐Khan; Erwin Bergmeier; Tomáš Černý; Milan Chytrý; Matteo Dainese; Jürgen Dengler; Jiri Dolezal; et al. (Global Ecology and Biogeography, 2023)
Aim Theoretical, experimental and observational studies have shown that biodiversity–ecosystem functioning (BEF) relationships are influenced by functional community structure through two mutually non‐exclusive mechanisms: (1) the dominance effect (which relates to the traits of the dominant species); and (2) the niche partitioning effect [which relates to functional diversity (FD)]. Although both mechanisms have been studied in plant communities and experiments at small spatial extents, it remains unclear whether evidence from small‐extent case studies translates into a generalizable macroecological pattern. Here, we evaluate dominance and niche partitioning effects simultaneously in grassland systems world‐wide. Location Two thousand nine hundred and forty‐one grassland plots globally. Time period 2000–2014. Major taxa studied Vascular plants. Methods We obtained plot‐based data on functional community structure from the global vegetation plot database “sPlot”, which combines species composition with plant trait data from the “TRY” database. We used data on the community‐weighted mean (CWM) and FD for 18 ecologically relevant plant traits. As an indicator of primary productivity, we extracted the satellite‐derived normalized difference vegetation index (NDVI) from MODIS. Using generalized additive models and deviation partitioning, we estimated the contributions of trait CWM and FD to the variation in annual maximum NDVI, while controlling for climatic variables and spatial structure. Results Grassland communities dominated by relatively tall species with acquisitive traits had higher NDVI values, suggesting the prevalence of dominance effects for BEF relationships. We found no support for niche partitioning for the functional traits analysed, because NDVI remained unaffected by FD. Most of the predictive power of traits was shared by climatic predictors and spatial coordinates. This highlights the importance of community assembly processes for BEF relationships in natural communities. Main conclusions Our analysis provides empirical evidence that plant functional community structure and global patterns in primary productivity are linked through the resource economics and size traits of the dominant species. This is an important test of the hypotheses underlying BEF relationships at the global scale.

Detection of SARS-CoV-2 RNA in wastewater and comparison to COVID-19 cases in two sewersheds, North Carolina, USA - Alyssa M. Grube; Collin K. Coleman; Connor D. LaMontagne; Megan E. Miller; Nikhil P. Kothegal; David A. Holcomb; A. Denene Blackwood; Thomas J. Clerkin; Marc L. Serre; Lawrence S. Engel; Virginia T. Guidry; Rachel T. Noble; et al. (Science of The Total Environment, 2023)

Fine particulate matter and incident coronary heart disease events up to 10 years of follow-up among Deepwater Horizon oil spill workers - Dazhe Chen; Dale P. Sandler; Alexander P. Keil; Gerardo Heiss; Eric A. Whitsel; Gregory C. Pratt; Patricia A. Stewart; Mark R. Stenzel; Caroline P. Groth; Sudipto Banerjee; Tran B. Huynh; Jessie K. Edwards; et al. (Environmental Research, 2023)

Geographic patterns of tree dispersal modes in Amazonia and their ecological correlates - Diego F. Correa; Pablo R. Stevenson; Maria Natalia Umaña; Luiz de Souza Coelho; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Iêda Leão do Amaral; Florian Wittmann; Francisca Dionízia de Almeida Matos; Carolina V. Castilho; Oliver L. Phillips; Juan Ernesto Guevara; et al. (Global Ecology and Biogeography, 2023)
Aim To investigate the geographic patterns and ecological correlates in the geographic distribution of the most common tree dispersal modes in Amazonia (endozoochory, synzoochory, anemochory and hydrochory). We examined if the proportional abundance of these dispersal modes could be explained by the availability of dispersal agents (disperser‐availability hypothesis) and/or the availability of resources for constructing zoochorous fruits (resource‐availability hypothesis). Time period Tree‐inventory plots established between 1934 and 2019. Major taxa studied Trees with a diameter at breast height (DBH) ≥ 9.55 cm. Location Amazonia, here defined as the lowland rain forests of the Amazon River basin and the Guiana Shield. Methods We assigned dispersal modes to a total of 5433 species and morphospecies within 1877 tree‐inventory plots across terra‐firme, seasonally flooded, and permanently flooded forests. We investigated geographic patterns in the proportional abundance of dispersal modes. We performed an abundance‐weighted mean pairwise distance (MPD) test and fit generalized linear models (GLMs) to explain the geographic distribution of dispersal modes. Results Anemochory was significantly, positively associated with mean annual wind speed, and hydrochory was significantly higher in flooded forests. Dispersal modes did not consistently show significant associations with the availability of resources for constructing zoochorous fruits. A lower dissimilarity in dispersal modes, resulting from a higher dominance of endozoochory, occurred in terra‐firme forests (excluding podzols) compared to flooded forests. Main conclusions The disperser‐availability hypothesis was well supported for abiotic dispersal modes (anemochory and hydrochory). The availability of resources for constructing zoochorous fruits seems an unlikely explanation for the distribution of dispersal modes in Amazonia. The association between frugivores and the proportional abundance of zoochory requires further research, as tree recruitment not only depends on dispersal vectors but also on conditions that favour or limit seedling recruitment across forest types.

Seagrass ecosystem multifunctionality under the rise of a flagship marine megaherbivore - Marjolijn J. A. Christianen; Fee O. H. Smulders; Jan Arie Vonk; Leontine E. Becking; Tjeerd J. Bouma; Sabine M. Engel; Rebecca K. James; Mabel I. Nava; Jaco C. de Smit; Jurjan P. van der Zee; Per J. Palsbøll; Elisabeth S. Bakker (Global Change Biology, 2023)
Large grazers (megaherbivores) have a profound impact on ecosystem functioning. However, how ecosystem multifunctionality is affected by changes in megaherbivore populations remains poorly understood. Understanding the total impact on ecosystem multifunctionality requires an integrative ecosystem approach, which is especially challenging to obtain in marine systems. We assessed the effects of experimentally simulated grazing intensity scenarios on ecosystem functions and multifunctionality in a tropical Caribbean seagrass ecosystem. As a model, we selected a key marine megaherbivore, the green turtle, whose ecological role is rapidly unfolding in numerous foraging areas where populations are recovering through conservation after centuries of decline, with an increase in recorded overgrazing episodes. To quantify the effects, we employed a novel integrated index of seagrass ecosystem multifunctionality based upon multiple, well‐recognized measures of seagrass ecosystem functions that reflect ecosystem services. Experiments revealed that intermediate turtle grazing resulted in the highest rates of nutrient cycling and carbon storage, while sediment stabilization, decomposition rates, epifauna richness, and fish biomass are highest in the absence of turtle grazing. In contrast, intense grazing resulted in disproportionally large effects on ecosystem functions and a collapse of multifunctionality. These results imply that (i) the return of a megaherbivore can exert strong effects on coastal ecosystem functions and multifunctionality, (ii) conservation efforts that are skewed toward megaherbivores, but ignore their key drivers like predators or habitat, will likely result in overgrazing‐induced loss of multifunctionality, and (iii) the multifunctionality index shows great potential as a quantitative tool to assess ecosystem performance. Considerable and rapid alterations in megaherbivore abundance (both through extinction and conservation) cause an imbalance in ecosystem functioning and substantially alter or even compromise ecosystem services that help to negate global change effects. An integrative ecosystem approach in environmental management is urgently required to protect and enhance ecosystem multifunctionality.

Declining morphological diversity in snakefly larvae during last 100 million years - Joachim T. Haug; Michael S. Engel; Patrick Mendes dos Santos; Gideon T. Haug; Patrick Müller; Carolin Haug (PalZ, 2022)
Raphidioptera, the group of snakeflies, is a rather species-poor in-group of Holometabola. Yet, fossils of snakeflies indicate that the group was more diverse in the past. Here we compare the morphological diversity of snakefly larvae over time. Snakefly larvae are well represented in Cretaceous and Eocene ambers facilitating such a comparison. We used measurements of discrete dimensions as a basis for comparison. This reveals a larger diversity of snakefly larvae in the Cretaceous, especially in relation to head shapes and morphology of the antennae, which were much more variable. In particular, some Cretaceous larvae possessed greatly elongated head capsules and uniquely long and prominent antennae, unparalleled among modern forms. Already by the Eocene, snakefly larvae were less variable than those of the Cretaceous, although some still possessed longer antennae than modern-day larvae. The loss of morphological diversity supports the already well-established loss of taxonomic diversity in the group across time. Quite likely, this also indicates a loss of ecological diversity. These results are comparable to losses in different lineages of the closely related group Neuroptera.

Local biodiversity change reflects interactions among changing abundance, evenness, and richness - Shane A. Blowes; Gergana N. Daskalova; Maria Dornelas; Thore Engel; Nicholas J. Gotelli; Anne E. Magurran; Inês S. Martins; Brian McGill; Daniel J. McGlinn; Alban Sagouis; Hideyasu Shimadzu; Sarah R. Supp; et al. (Ecology, 2022)
Biodiversity metrics often integrate data on the presence and abundance of multiple species. Yet our understanding of covariation between changes to the numbers of individuals, the evenness of species relative abundances, and the total number of species remains limited. Using individual‐based rarefaction curves, we show how expected positive relationships among changes in abundance, evenness and richness arise, and how they can break down. We then examined interdependencies between changes in abundance, evenness and richness in more than 1100 assemblages sampled either through time or across space. As predicted, richness changes were greatest when abundance and evenness changed in the same direction, and countervailing changes in abundance and evenness acted to constrain the magnitude of changes in species richness. Site‐to‐site differences in abundance, evenness, and richness were often decoupled, and pairwise relationships between these components across assemblages were weak. In contrast, changes in species richness and relative abundance were strongly correlated for assemblages varying through time. Temporal changes in local biodiversity showed greater inertia and stronger relationships between the component changes when compared to site‐to‐site variation. Overall, local variation in assemblage diversity was rarely due to repeated passive samples from an approximately static species abundance distribution. Instead, changing species relative abundances often dominated local variation in diversity. Moreover, how changing relative abundances combined with changes to total abundance frequently determined the magnitude of richness changes. Embracing the interdependencies between changing abundance, evenness and richness can provide new information to better understand biodiversity change in the Anthropocene.

Current and future distributions of a native Andean bumble bee - Andressa C. Nascimento; José Montalva; John S. Ascher; Michael S. Engel; Daniel P. Silva (Journal of Insect Conservation, 2022)

Age-Dependent Dispersal and Relatedness in Tiger Sharks (Galeocerdo cuvier) - Margaret A. McClain; Neil Hammerschlag; Austin J. Gallagher; J. Marcus Drymon; R. Dean Grubbs; Tristan L. Guttridge; Matthew J. Smukall; Bryan S. Frazier; Toby S. Daly-Engel (Frontiers in Marine Science, 2022)
Understanding dispersal in large marine fauna is necessary for conservation, but movement patterns often vary widely by sex and life stage. In sharks, genetic studies have shown evidence of widespread male-biased dispersal, though tagging and tracking studies on the same populations show both sexes using site fidelity, including philopatry, and moving similar distances. We used a suite of microsatellite loci and DNA samples from 362 previously-tagged tiger sharks (Galeocerdo cuvier) in the northwestern Atlantic, including a large number of residential juveniles, to evaluate reproductive dispersal in light of demographic and published tracking data. We found that lumping size classes together resulted in genetic panmixia across sites, but systematic removal of large individuals showed significant population-level differentiation and three separate population clusters among juveniles less than 260 cm total length. Tests for relatedness found that 8.9% of our sample set was composed of first-order related pairs (N = 16), including several full siblings from different litters, a sign of multi-cycle genetic monogamy which carries implications for effective population size. By mapping genetic assignments of juveniles, we identified a signature of fine-scale genetic structure suggesting broad biparental site fidelity to reproductive habitat in the northeast Gulf of Mexico, which is concordant with both genetic and tracking data. Taken together, these findings demonstrate how lumping individuals from different life stages in genetic studies may obscure fine-scale genetic structure, confounding future conservation efforts.

Involvement of serotonergic neurotransmission in the antidepressant-like effect elicited by cholecalciferol in the chronic unpredictable stress model in mice - Vivian B. Neis; Isabel Werle; Morgana Moretti; Priscila B. Rosa; Anderson Camargo; Yasmim de O. Dalsenter; Nicolle Platt; Axel F. Rosado; William D. Engel; Gudrian Ricardo L. de Almeida; Ingrid Selhorst; Alcir Luiz Dafre; et al. (Metabolic Brain Disease, 2022)

Reviewing the genetic evidence for sex-biased dispersal in elasmobranchs - Nicole M. Phillips; Floriaan Devloo-Delva; Carly McCall; Toby S. Daly-Engel (Reviews in Fish Biology and Fisheries, 2021)

Site and plant community parameters drive the effect of vegetation on litterfall and nutrient inputs in restored tropical forests - Deivid L. Machado; Vera L. Engel; Diego S. Podadera; Luciane M. Sato; Ron G. M. de Goede; Luiz F. D. de Moraes; John A. Parrotta (Plant and Soil, 2021)

Genetic evidence supports a range extension for the Brazilian cownose ray Rhinoptera brasiliensis in the western North Atlantic - Helen K. Weber; Christian M. Jones; Matthew J. Ajemian; Michael P. McCallister; Brent L. Winner; Gregg R. Poulakis; Dana M. Bethea; Lisa D. Hollensead; Daniel Zapf; John D. Swenson; Jill M. Hendon; Toby S. Daly‐Engel; et al. (Journal of Fish Biology, 2021)
We report 24 new records of the Brazilian cownose ray Rhinoptera brasiliensis outside its accepted geographic range. Sequencing of a 442‐base pair portion of the mitochondrial NADH dehydrogenase subunit 2 gene for 282 Rhinoptera samples revealed eight records off the east coast of the USA and 16 from the eastern Gulf of Mexico. Both sexes of all life stages were documented in all seasons over multiple years in the Indian River and Lake Worth lagoons, Florida, indicating that their range extends further in the western North Atlantic than previously described.

A new and diverse paleofauna of the extinct snakefly family Baissopteridae from the mid-Cretaceous of Myanmar (Raphidioptera) - Xiumei Lu; Weiwei Zhang; Bo Wang; Michael S. Engel; Xingyue Liu (Organisms Diversity & Evolution, 2020)

A review of a decade of lessons from one of the world’s largest MPAs: conservation gains and key challenges - Graeme C. Hays; Heather J. Koldewey; Samantha Andrzejaczek; Martin J. Attrill; Shanta Barley; Daniel T. I. Bayley; Cassandra E. Benkwitt; Barbara Block; Robert J. Schallert; Aaron B. Carlisle; Pete Carr; Taylor K. Chapple; et al. (Marine Biology, 2020)

Leaf-mimicking katydids from the Middle Miocene of Yunnan, southwestern China (Orthoptera: Tettigoniidae) - André Nel; Bo Wang; Michael S. Engel; Jian Huang; Lin-Bo Jia; Tao Su; Torsten Wappler (PalZ, 2020)

Soothsaying DOM: A Current Perspective on the Future of Oceanic Dissolved Organic Carbon - Sasha Wagner; Florence Schubotz; Karl Kaiser; Christian Hallmann; Hannelore Waska; Pamela E. Rossel; Roberta Hansman; Marcus Elvert; Jack J. Middelburg; Anja Engel; Thomas M. Blattmann; Teresa S. Catalá; et al. (Frontiers in Marine Science, 2020)

Temperature change as a driver of spatial patterns and long‐term trends in chironomid (Insecta: Diptera) diversity - Stefan Engels; Andrew S. Medeiros; Yarrow Axford; Stephen J. Brooks; Oliver Heiri; Tomi P. Luoto; Larisa Nazarova; David F. Porinchu; Roberto Quinlan; Angela E. Self (Global Change Biology, 2020)
Anthropogenic activities have led to a global decline in biodiversity, and monitoring studies indicate that both insect communities and wetland ecosystems are particularly affected. However, there is a need for long‐term data (over centennial or millennial timescales) to better understand natural community dynamics and the processes that govern the observed trends. Chironomids (Insecta: Diptera: Chironomidae) are often the most abundant insects in lake ecosystems, sensitive to environmental change, and, because their larval exoskeleton head capsules preserve well in lake sediments, they provide a unique record of insect community dynamics through time. Here, we provide the results of a metadata analysis of chironomid diversity across a range of spatial and temporal scales. First, we analyse spatial trends in chironomid diversity using Northern Hemispheric data sets overall consisting of 837 lakes. Our results indicate that in most of our data sets, summer temperature ( T jul ) is strongly associated with spatial trends in modern‐day chironomid diversity. We observe a strong increase in chironomid alpha diversity with increasing T jul in regions with present‐day T jul between 2.5 and 14°C. In some areas with T jul > 14°C, chironomid diversity stabilizes or declines. Second, we demonstrate that the direction and amplitude of change in alpha diversity in a compilation of subfossil chironomid records spanning the last glacial–interglacial transition (~15,000–11,000 years ago) are similar to those observed in our modern data. A compilation of Holocene records shows that during phases when the amplitude of temperature change was small, site‐specific factors had a greater influence on the chironomid fauna obscuring the chironomid diversity–temperature relationship. Our results imply expected overall chironomid diversity increases in colder regions such as the Arctic under sustained global warming, but with complex and not necessarily predictable responses for individual sites.

Developing Large-Scale Research in Response to an Oil Spill Disaster: a Case Study - Richard K. Kwok; Aubrey K. Miller; Kaitlyn B. Gam; Matthew D. Curry; Steven K. Ramsey; Aaron Blair; Lawrence S. Engel; Dale P. Sandler (Current Environmental Health Reports, 2019)

Genomic changes underlying host specialization in the bee gut symbiont Lactobacillus Firm5 - Kirsten M. Ellegaard; Silvia Brochet; German Bonilla‐Rosso; Olivier Emery; Natasha Glover; Noushin Hadadi; Kamil S. Jaron; Jan R. van der Meer; Marc Robinson‐Rechavi; Vladimir Sentchilo; Florian Tagini; Philipp Engel (Molecular Ecology, 2019)
Bacteria that engage in long‐standing associations with particular hosts are expected to evolve host‐specific adaptations that limit their capacity to thrive in other environments. Consistent with this, many gut symbionts seem to have a limited host range, based on community profiling and phylogenomics. However, few studies have experimentally investigated host specialization of gut symbionts and the underlying mechanisms have largely remained elusive. Here, we studied host specialization of a dominant gut symbiont of social bees, Lactobacillus Firm5. We show that Firm5 strains isolated from honey bees and bumble bees separate into deep‐branching host‐specific phylogenetic lineages. Despite their divergent evolution, colonization experiments show that bumble bee strains are capable of colonizing the honey bee gut. However, they were less successful than honey bee strains, and competition with honey bee strains completely abolished their colonization. In contrast, honey bee strains of divergent phylogenetic lineages were able to coexist within individual bees. This suggests that both host selection and interbacterial competition play important roles in host specialization. Using comparative genomics of 27 Firm5 isolates, we found that the genomes of honey bee strains harbour more carbohydrate‐related functions than bumble bee strains, possibly providing a competitive advantage in the honey bee gut. Remarkably, most of the genes encoding carbohydrate‐related functions were not conserved among the honey bee strains, which suggests that honey bees can support a metabolically more diverse community of Firm5 strains than bumble bees. These findings advance our understanding of the genomic changes underlying host specialization.

Resurrection of the sixgill shark Hexanchus vitulus Springer & Waller, 1969 (Hexanchiformes, Hexanchidae), with comments on its distribution in the northwest Atlantic Ocean - Toby S. Daly-Engel; Ivy E. Baremore; R. Dean Grubbs; Simon J. B. Gulak; Rachel T. Graham; Michael P. Enzenauer (Marine Biodiversity, 2019)

Current and future ranges of an elusive North American insect using species distribution models - Daniel P. Silva; André F. A. Andrade; João P. J. Oliveira; Danielle M. Morais; Julya E. A. Vieira; Michael S. Engel (Journal of Insect Conservation, 2019)

Compositional response of Amazon forests to climate change - Adriane Esquivel‐Muelbert; Timothy R. Baker; Kyle G. Dexter; Simon L. Lewis; Roel J. W. Brienen; Ted R. Feldpausch; Jon Lloyd; Abel Monteagudo‐Mendoza; Luzmila Arroyo; Esteban Álvarez-Dávila; Niro Higuchi; Beatriz S. Marimon; et al. (Global Change Biology, 2019)
Most of the planet's diversity is concentrated in the tropics, which includes many regions undergoing rapid climate change. Yet, while climate‐induced biodiversity changes are widely documented elsewhere, few studies have addressed this issue for lowland tropical ecosystems. Here we investigate whether the floristic and functional composition of intact lowland Amazonian forests have been changing by evaluating records from 106 long‐term inventory plots spanning 30 years. We analyse three traits that have been hypothesized to respond to different environmental drivers (increase in moisture stress and atmospheric CO 2 concentrations): maximum tree size, biogeographic water‐deficit affiliation and wood density. Tree communities have become increasingly dominated by large‐statured taxa, but to date there has been no detectable change in mean wood density or water deficit affiliation at the community level, despite most forest plots having experienced an intensification of the dry season. However, among newly recruited trees, dry‐affiliated genera have become more abundant, while the mortality of wet‐affiliated genera has increased in those plots where the dry season has intensified most. Thus, a slow shift to a more dry‐affiliated Amazonia is underway, with changes in compositional dynamics (recruits and mortality) consistent with climate‐change drivers, but yet to significantly impact whole‐community composition. The Amazon observational record suggests that the increase in atmospheric CO 2 is driving a shift within tree communities to large‐statured species and that climate changes to date will impact forest composition, but long generation times of tropical trees mean that biodiversity change is lagging behind climate change.

Future Research Directions on the “Elusive” White Shark - Charlie Huveneers; Kirin Apps; Edgar E. Becerril-García; Barry Bruce; Paul A. Butcher; Aaron B. Carlisle; Taylor K. Chapple; Heather M. Christiansen; Geremy Cliff; Tobey H. Curtis; Toby S. Daly-Engel; Heidi Dewar; et al. (Frontiers in Marine Science, 2018)

Genetic variants in components of the NALCN–UNC80–UNC79 ion channel complex cause a broad clinical phenotype (NALCN channelopathies) - Nuria C. Bramswig; Aida M. Bertoli-Avella; Beate Albrecht; Aida I. Al Aqeel; Amal Alhashem; Nouriya Al-Sannaa; Maissa Bah; Katharina Bröhl; Christel Depienne; Nathalie Dorison; Diane Doummar; Nadja Ehmke; et al. (Human Genetics, 2018)

The gut microbiome is associated with behavioural task in honey bees - J. C. Jones; C. Fruciano; J. Marchant; F. Hildebrand; S. Forslund; P. Bork; P. Engel; W. O. H. Hughes (Insectes Sociaux, 2018)

De novo mutations in MED13, a component of the Mediator complex, are associated with a novel neurodevelopmental disorder - Lot Snijders Blok; Susan M. Hiatt; Kevin M. Bowling; Jeremy W. Prokop; Krysta L. Engel; J. Nicholas Cochran; E. Martina Bebin; Emilia K. Bijlsma; Claudia A. L. Ruivenkamp; Paulien Terhal; Marleen E. H. Simon; Rosemarie Smith; et al. (Human Genetics, 2018)

Temporal stability and mixed-stock analyses of humpback whales (Megaptera novaeangliae) in the nearshore waters of the Western Antarctic Peninsula - G. R. Albertson; A. S. Friedlaender; D. J. Steel; A. Aguayo-Lobo; S. L. Bonatto; S. Caballero; R. Constantine; A. L. Cypriano-Souza; M. H. Engel; C. Garrigue; L. Flórez-González; D. W. Johnston; et al. (Polar Biology, 2018)

Brain-Defective Insulin Signaling Is Associated to Late Cognitive Impairment in Post-Septic Mice - Fernanda S. Neves; Patrícia T. Marques; Fernanda Barros‑Aragão; José Bruno Nunes; Aline M. Venancio; Danielle Cozachenco; Rudimar L. Frozza; Giselle F. Passos; Robson Costa; Jade de Oliveira; Daiane F. Engel; Andreza F. De Bem; et al. (Molecular Neurobiology, 2018)

Late Holocene changes in vegetation and atmospheric circulation at Lake Uddelermeer (The Netherlands) reconstructed using lipid biomarkers and compound‐specific δD analysis - V. van den Bos; S. Engels; S. J. P. Bohncke; C. Cerli; B. Jansen; K. Kalbitz; F. Peterse; H. Renssen; D. Sachse (Journal of Quaternary Science, 2018)
We reconstructed middle to late Holocene changes in atmospheric circulation patterns and vegetation in north‐west Europe by applying novel geochemical techniques to the sediment record of Lake Uddelermeer (The Netherlands). A comparison of higher plant‐derived leaf wax n ‐alkane distributions archived in the lake sediments with those in living plant material, combined with palynological analysis, indicates that the vegetation immediately surrounding the lake became more open at 3150 cal a BP , while the regional vegetation responded more gradually and ∼650 years later. Our record of the hydrogen isotopic composition of plant leaf waxes (δD wax ) shows a deuterium enrichment starting from 3500 cal a BP , which we interpret as a change in atmospheric circulation. A similar δD wax record from nearby Meerfelder Maar (Germany) shows an opposite trend around this time, which could be explained by a change in sea‐level pressure resembling a negative North Atlantic Oscillation phase. This could account for depleted δD values of precipitation at Meerfelder Maar, while confounding factors related to the more maritime position of Uddelermeer cause the opposite shift there.

Latitude, temperature, and habitat complexity predict predation pressure in eelgrass beds across the Northern Hemisphere - Pamela L. Reynolds; John J. Stachowicz; Kevin Hovel; Christoffer Boström; Katharyn Boyer; Mathieu Cusson; Johan S. Eklöf; Friederike G. Engel; Aschwin H. Engelen; Britas Klemens Eriksson; F. Joel Fodrie; John N. Griffin; et al. (Ecology, 2018)
Latitudinal gradients in species interactions are widely cited as potential causes or consequences of global patterns of biodiversity. However, mechanistic studies documenting changes in interactions across broad geographic ranges are limited. We surveyed predation intensity on common prey (live amphipods and gastropods) in communities of eelgrass ( Zostera marina ) at 48 sites across its Northern Hemisphere range, encompassing over 37° of latitude and four continental coastlines. Predation on amphipods declined with latitude on all coasts but declined more strongly along western ocean margins where temperature gradients are steeper. Whereas in situ water temperature at the time of the experiments was uncorrelated with predation, mean annual temperature strongly positively predicted predation, suggesting a more complex mechanism than simply increased metabolic activity at the time of predation. This large‐scale biogeographic pattern was modified by local habitat characteristics; predation declined with higher shoot density both among and within sites. Predation rates on gastropods, by contrast, were uniformly low and varied little among sites. The high replication and geographic extent of our study not only provides additional evidence to support biogeographic variation in predation intensity, but also insight into the mechanisms that relate temperature and biogeographic gradients in species interactions.

Use of phytoproductivity data in the choice of native plant species to restore a degraded coal mining site amended with a stabilized industrial organic sludge - Claudete G. Chiochetta; Hela Toumi; Renata F. S. Böhm; Fernanda Engel; Gabriel Poyer-Radetski; Leonardo R. Rörig; Fabrizio Adani; Claudemir M. Radetski (Environmental Science and Pollution Research, 2017)

Genotypic and phenotypic changes in wild barley (Hordeum vulgare subsp. spontaneum) during a period of climate change in Jordan - I. Thormann; P. Reeves; S. Thumm; A. Reilley; J. M. M. Engels; C. M. Biradar; U. Lohwasser; A. Börner; K. Pillen; C. M. Richards (Genetic Resources and Crop Evolution, 2017)

Charles D. Michener (1918–2015): a life among the bees - Michael S. Engel (Arthropod-Plant Interactions, 2017)

The Ocean's Vital Skin: Toward an Integrated Understanding of the Sea Surface Microlayer - Anja Engel; Hermann W. Bange; Michael Cunliffe; Susannah M. Burrows; Gernot Friedrichs; Luisa Galgani; Hartmut Herrmann; Norbert Hertkorn; Martin Johnson; Peter S. Liss; Patricia K. Quinn; Markus Schartau; et al. (Frontiers in Marine Science, 2017)

Efficacy and safety of metformin and sitagliptin based triple antihyperglycemic therapy (STRATEGY): a multicenter, randomized, controlled, non-inferiority clinical trial - Wen Xu; Yiming Mu; Jiajun Zhao; Dalong Zhu; Qiuhe Ji; Zhiguang Zhou; Bin Yao; Anhua Mao; Samuel S. Engel; Bin Zhao; Yan Bi; Longyi Zeng; et al. (Science China Life Sciences, 2017)

Identification of new TRIP12 variants and detailed clinical evaluation of individuals with non-syndromic intellectual disability with or without autism - Nuria C. Bramswig; H.-J. Lüdecke; M. Pettersson; B. Albrecht; R. A. Bernier; K. Cremer; E. E. Eichler; D. Falkenstein; J. Gerdts; S. Jansen; A. Kuechler; M. Kvarnung; et al. (Human Genetics, 2017)

A family-based study of gene variants and maternal folate and choline in neuroblastoma: a report from the Children’s Oncology Group - Angela L. Mazul; Anna Maria Siega-Riz; Clarice R. Weinberg; Stephanie M. Engel; Fei Zou; Kathryn S. Carrier; Patricia V. Basta; Zalman Vaksman; John M. Maris; Sharon J. Diskin; Charlene Maxen; Arlene Naranjo; et al. (Cancer Causes & Control, 2016)

The first Mesozoic microwhip scorpion (Palpigradi): a new genus and species in mid-Cretaceous amber from Myanmar - Michael S. Engel; Laura C. V. Breitkreuz; Chenyang Cai; Mabel Alvarado; Dany Azar; Diying Huang (The Science of Nature, 2016)

Distributional modeling of Mantophasmatodea (Insecta: Notoptera): a preliminary application and the need for future sampling - Daniel P. Silva; Zander A. Spigoloni; Lucas M. Camargos; André Felipe Alves de Andrade; Paulo De Marco; Michael S. Engel (Organisms Diversity & Evolution, 2016)

Influence of Removal of a Non-native Tree Species Mimosa caesalpiniifolia Benth. on the Regenerating Plant Communities in a Tropical Semideciduous Forest Under Restoration in Brazil - Diego S. Podadera; Vera L. Engel; John A. Parrotta; Deivid L. Machado; Luciane M. Sato; Giselda Durigan (Environmental Management, 2015)

Wideband phase locking to modulated whisker vibration point to a temporal code for texture in the rat’s barrel cortex - Tobias A. S. Ewert; Johannes Möller; Andreas K. Engel; Christiane Vahle-Hinz (Experimental Brain Research, 2015)

In Vivo Quantification of the Apical Fixation Forces of Different Mitral Valved Stent Designs in the Beating Heart - S. Pokorny; K. Huenges; A. Engel; J. Gross; D. Frank; M. M. Morlock; J. Cremer; G. Lutter (Annals of Biomedical Engineering, 2015)

De novo mutations in beta-catenin (CTNNB1) appear to be a frequent cause of intellectual disability: expanding the mutational and clinical spectrum - Alma Kuechler; Marjolein H. Willemsen; Beate Albrecht; Carlos A. Bacino; Dennis W. Bartholomew; Hans van Bokhoven; Marie Jose H. van den Boogaard; Nuria Bramswig; Christian Büttner; Kirsten Cremer; Johanna Christina Czeschik; Hartmut Engels; et al. (Human Genetics, 2015)

A new trap-jaw ant species of the genus Odontomachus (Hymenoptera: Formicidae: Ponerinae) from the Early Miocene (Burdigalian) of the Czech Republic - Torsten Wappler; Gennady M. Dlussky; Michael S. Engel; Jakub Prokop; Stanislav Knor (PalZ, 2014)

New bethylid and chrysidid wasps (Hymenoptera: Chrysidoidea) from Canadian Late Cretaceous amber - Ryan C. McKellar; Michael S. Engel (PalZ, 2014)

A Semi-mechanistic Model for the Effects of a Novel Glucagon Receptor Antagonist on Glucagon and the Interaction Between Glucose, Glucagon, and Insulin Applied to Adaptive Phase II Design - Joanna Z. Peng; William S. Denney; Bret J. Musser; Rong Liu; Kuenhi Tsai; Lanyan Fang; Marc L. Reitman; Matthew D. Troyer; Samuel S. Engel; Lei Xu; Aubrey Stoch; Julie A. Stone; et al. (The AAPS Journal, 2014)

A tailored implementation strategy to reduce the duration of intravenous antibiotic treatment in community-acquired pneumonia: a controlled before-and-after study - M. F. Engel; A. H. W. Bruns; M. E. J. L. Hulscher; C. A. J. M. Gaillard; S. U. C. Sankatsing; F. Teding van Berkhout; M. H. Emmelot-Vonk; E. M. Kuck; M. H. M. Steeghs; J. H. den Breeijen; R. K. Stellato; A. I. M. Hoepelman; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Adolescents’ use of nicotine replacement therapy for smoking cessation: predictors of compliance trajectories - Charlotte S. Scherphof; Regina J. J. M. van den Eijnden; Peter Lugtig; Rutger C. M. E. Engels; Wilma A. M. Vollebergh (Psychopharmacology, 2014)

Antiphasic 40 Hz Oscillatory Current Stimulation Affects Bistable Motion Perception - Daniel Strüber; Stefan Rach; Sina A. Trautmann-Lengsfeld; Andreas K. Engel; Christoph S. Herrmann (Brain Topography, 2014)

Mechanisms linking plant community properties to soil aggregate stability in an experimental grassland plant diversity gradient - G. Pérès; D. Cluzeau; S. Menasseri; J. F. Soussana; H. Bessler; C. Engels; M. Habekost; G. Gleixner; A. Weigelt; W. W. Weisser; S. Scheu; N. Eisenhauer (Plant and Soil, 2013)

Greater past disparity and diversity hints at ancient migrations of European honey bee lineages into Africa and Asia - Ulrich Kotthoff; Torsten Wappler; Michael S. Engel (Journal of Biogeography, 2013)
Aim We re‐evaluated the proposition based on the present‐day distribution of honey bees (genus A pis ) that their centre of origin resides in Asia, with subsequent migration and diversification into E urope and A sia. In our research, we considered the so‐far largely ignored fossils distributed through a variety of late P alaeogene ( O ligocene) and early Neogene ( M iocene) deposits, aiming at a synthesis of both present‐day and past honey bee distribution. Location Northern Hemisphere, A frica, S outheast A sia. Methods We examined the morphological diversity (also termed ‘disparity’) and affinities of the full living and fossil diversity of honey bees ranging from their earliest origins to the present day. Based on the fossil record and present‐day distribution of species, considering continental drift from the Oligocene until today, we have established an evolution and migration scenario for the genus A pis . Results The fossil record of A pis demonstrates a diversity that is predominantly European in origin, particularly among the most basal species of the genus. Honey bees exhibited a greater morphological disparity during the Oligocene and, particularly, the M iocene epochs, a time when the principal lineages were established. Contradicting earlier propositions, the geological models allowed a migration via western E urope to north‐western Africa during the M iocene, and the fossil record corroborates such a migration. Main conclusions From the full complement of available data, A pis apparently originated in Europe, spreading from there into A sia, A frica and N orth A merica, with subsequent diversification in the former two regions and extinction in the latter. The western honey bee, A pis mellifera , descended from E uropean ancestors that probably migrated from western E urope to A frica during the late M iocene and re‐immigrated into E urope during the Holocene and possibly preceding interglacials.

A comparison of the strength of biodiversity effects across multiple functions - Eric Allan; Wolfgang W. Weisser; Markus Fischer; Ernst-Detlef Schulze; Alexandra Weigelt; Christiane Roscher; Jussi Baade; Romain L. Barnard; Holger Beßler; Nina Buchmann; Anne Ebeling; Nico Eisenhauer; et al. (Oecologia, 2013)

Positive urinary antigen tests for Streptococcus pneumoniae in community-acquired pneumonia: a 7-year retrospective evaluation of health care cost and treatment consequences - M. F. Engel; M. Velzen; A. I. M. Hoepelman; S. Thijsen; J. J. Oosterheert (European Journal of Clinical Microbiology & Infectious Diseases, 2013)

17 novel polymorphic microsatellite markers for the giant water bug, Abedus herberti (Belostomatidae) - T. S. Daly-Engel; R. L. Smith; D. S. Finn; M. E. Knoderbane; I. C. Phillipsen; D. A. Lytle (Conservation Genetics Resources, 2012)

Differential BDNF Responses of Triple Versus Dual Reuptake Inhibition in Neuronal and Astrocytoma Cells as well as in Rat Hippocampus and Prefrontal Cortex - Jos Prickaerts; Jochen De Vry; Janneke Boere; Gunter Kenis; Maria S. Quinton; Sharon Engel; Larry Melnick; Rudy Schreiber (Journal of Molecular Neuroscience, 2012)

Validation of three BRCA1/2 mutation-carrier probability models Myriad, BRCAPRO and BOADICEA in a population-based series of 183 German families - S. M. Schneegans; A. Rosenberger; U. Engel; M. Sander; G. Emons; M. Shoukier (Familial Cancer, 2012)

Is the Great Barracuda (Sphyraena barracuda) a reef fish or a pelagic fish? The phylogeographic perspective - Toby S. Daly-Engel; John E. Randall; Brian W. Bowen (Marine Biology, 2012)

Assessing the potential for post‐copulatory sexual selection in elasmobranchs - J. L. Fitzpatrick; R. M. Kempster; T. S. Daly‐Engel; S. P. Collin; J. P. Evans (Journal of Fish Biology, 2012)
This review highlights the potential role that post‐copulatory sexual selection plays in elasmobranch reproductive systems and the utility of this group to further understanding of evolutionary responses to the post‐copulatory processes of sperm competition and cryptic female choice. The growing genetic evidence for female multiple mating (polyandry) in elasmobranchs is summarized. While polyandry appears to be common in this group, rates of multiple paternity are highly variable between species suggesting that there is large variance in the strength of post‐copulatory sexual selection among elasmobranchs. Possible adaptations of traits important for post‐copulatory sexual selection are then considered. Particular emphasis is devoted to explore the potential for sperm competition and cryptic female choice to influence the evolution of testes size, sperm morphology, genital morphology and sperm storage organs. Finally, it is argued that future work should take advantage of the wealth of information on these reproductive traits already available in elasmobranchs to gain a better understanding of how post‐copulatory sexual selection operates in this group.

A Hydrological Budget (2002–2008) for a Large Subtropical Wetland Ecosystem Indicates Marine Groundwater Discharge Accompanies Diminished Freshwater Flow - Amartya K. Saha; Christopher S. Moses; René M. Price; Victor Engel; Thomas J. Smith; Gordon Anderson (Estuaries and Coasts, 2012)

A high-throughput solid phase screening method for identification of lignocellulose-degrading bacteria from environmental isolates - Jeffrey G. Gardner; Laura A. Zeitler; Wendy Jo S. Wigstrom; Kristine C. Engel; David H. Keating (Biotechnology Letters, 2012)

Description of an ancient social bee trapped in amber using diagnostic radioentomology - M. K. Greco; P. M. Welz; M. Siegrist; S. J. Ferguson; P. Gallmann; D. W. Roubik; M. S. Engel (Insectes Sociaux, 2011)

Tree–Grass Coexistence in the Everglades Freshwater System - Paolo D’Odorico; Vic Engel; Joel A. Carr; Steven F. Oberbauer; Michael S. Ross; Jay P. Sah (Ecosystems, 2011)

Crustose, calcareous algal bloom (Ramicrusta sp.) overgrowing scleractinian corals, gorgonians, a hydrocoral, sponges, and other algae in Lac Bay, Bonaire, Dutch Caribbean - C. E. Eckrich; M. S. Engel; R. B. J. Peachey (Coral Reefs, 2011)

Recommendations to improve identification of hereditary and familial colorectal cancer in Europe - H. F. A. Vasen; G. Möslein; A. Alonso; S. Aretz; I. Bernstein; L. Bertario; I. Blanco; S. Bulow; J. Burn; G. Capella; C. Colas; C. Engel; et al. (Familial Cancer, 2010)

Plant diversity effects on soil microorganisms support the singular hypothesis - N. Eisenhauer; H. Beßler; C. Engels; G. Gleixner; M. Habekost; A. Milcu; S. Partsch; A. C. W. Sabais; C. Scherber; S. Steinbeiss; A. Weigelt; W. W. Weisser; et al. (Ecology, 2010)
The global decline in biodiversity has generated concern over the consequences for ecosystem functioning and services. Although ecosystem functions driven by soil microorganisms such as plant productivity, decomposition, and nutrient cycling are of particular importance, interrelationships between plant diversity and soil microorganisms are poorly understood. We analyzed the response of soil microorganisms to variations in plant species richness (1–60) and plant functional group richness (1–4) in an experimental grassland system over a period of six years. Major abiotic and biotic factors were considered for exploring the mechanisms responsible for diversity effects. Further, microbial growth characteristics were assessed following the addition of macronutrients. Effects of plant diversity on soil microorganisms were most pronounced in the most diverse plant communities though differences only became established after a time lag of four years. Differences in microbial growth characteristics indicate successional changes from a disturbed (zymogeneous) to an established (autochthonous) microbial community four years after establishment of the experiment. Supporting the singular hypothesis for plant diversity, the results suggest that plant species are unique, each contributing to the functioning of the belowground system. The results reinforce the need for long‐term biodiversity experiments to fully appreciate consequences of current biodiversity loss for ecosystem functioning.

Maternally inherited architecture in tertiary leaf beetles: paleoichnology of cryptocephaline fecal cases in Dominican and Baltic amber - Caroline S. Chaboo; Michael S. Engel; Maria Lourdes Chamorro-Lacayo (The Science of Nature, 2009)

Direct and indirect fossil records of megachilid bees from the Paleogene of Central Europe (Hymenoptera: Megachilidae) - Sonja Wedmann; Torsten Wappler; Michael S. Engel (The Science of Nature, 2009)

A giant termite from the Late Miocene of Styria, Austria (Isoptera) - Michael S. Engel; Martin Gross (The Science of Nature, 2009)

Demise of reef-flat carbonate accumulation with late Holocene sea-level fall: evidence from Molokai, Hawaii - M. S. Engels; C. H. Fletcher; M. Field; C. L. Conger; C. Bochicchio (Coral Reefs, 2008)

Hennigian Phylogenetic Systematics and the ‘Groundplan’ vs. ‘Post-Groundplan’ Approaches: A Reply to Kukalová-Peck - Olivier Béthoux; Niels P. Kristensen; Michael S. Engel (Evolutionary Biology, 2008)

Mitochondrial DNA diversity of the Southwestern Atlantic humpback whale (Megaptera novaeangliae) breeding area off Brazil, and the potential connections to Antarctic feeding areas - Márcia H. Engel; Nelson J. R. Fagundes; Howard C. Rosenbaum; Matthew S. Leslie; Paulo H. Ott; Renata Schmitt; Eduardo Secchi; Luciano Dalla Rosa; Sandro Luis Bonatto (Conservation Genetics, 2008)

Intraregional variability in chironomid-inferred temperature estimates and the influence of river inundations on lacustrine chironomid assemblages - S. Engels; S. J. P. Bohncke; O. Heiri; M. Nyman (Journal of Paleolimnology, 2008)

Chironomid-based palaeotemperature estimates for northeast Finland during Oxygen Isotope Stage 3 - S. Engels; S. J. P. Bohncke; J. A. A. Bos; S. J. Brooks; O. Heiri; K. F. Helmens (Journal of Paleolimnology, 2008)

The influence of coastal topography, circulation patterns, and rafting in structuring populations of an intertidal alga - J. F. MUHLIN; C. R. ENGEL; R. STESSEL; R. A. WEATHERBEE; S. H. BRAWLEY (Molecular Ecology, 2008)
Understanding the dispersal processes that influence genetic structure in marine species requires estimating gene flow in a dynamic, fluid environment that is often poorly characterized at scales relevant to multiple dispersive stages (e.g. spores, gametes, zygotes, larvae, adults). We examine genetic structure in the marine alga Fucus vesiculosus L., which inhabits moderately exposed shores in the northern Atlantic but releases gametes only under sunny, calm conditions. We predicted genetic structure would correlate with coastal topography because weather frequently varies across coastal promontories on the Maine shore when F. vesiculosus is reproductive, which causes one side to experience high levels of water motion (= no gamete release) while one side is calm (= gamete release). Furthermore, we expected that the effect of low dispersal capacities of gametes and zygotes would result in spatial genetic structure over short distances. Using surface drifters, we characterized near‐shore circulation patterns around the study sites to investigate whether directionality of gene flow was correlated with directionality of currents. We found significant genetic differentiation among sites sampled at two different peninsulas, but patterns of differentiation were unrelated to coastal topography and there was no within‐site spatial structuring. Our genetic and near‐shore circulation data, combined with an examination of gamete longevity, support the dependency of gene flow on storm‐detached, rafting, reproductive adults. This study highlights the significance of rafting as a mechanism for structuring established populations of macroalgae and associated biota and demonstrates the importance of coupling population genetics’ research with relevant hydrodynamic studies.

In situ detection of novel Acidobacteria in microbial mats from a chemolithoautotrophically based cave ecosystem (Lower Kane Cave, WY, USA) - Daniela B. Meisinger; Johannes Zimmermann; Wolfgang Ludwig; Karl‐Heinz Schleifer; Gerhard Wanner; Michael Schmid; Philip C. Bennett; Annette S. Engel; Natuschka M. Lee (Environmental Microbiology, 2007)
Summary Lower Kane Cave, Wyoming (USA), has hydrogen sulfide‐bearing springs that discharge into the cave passage. The springs and cave stream harbour white filamentous microbial mats dominated by Epsilonproteobacteria . Recently, novel 16S rRNA gene sequences from the phylum Acidobacteria , subgroup 7, were found in these cave mats. Although Acidobacteria are ubiquitously distributed in many terrestrial and marine habitats, little is known about their ecophysiology. To investigate this group in Lower Kane Cave in more detail, a full‐cycle rRNA approach was applied based on 16S and 23S rRNA gene clone libraries and the application of novel probes for fluorescence in situ hybridization . The 16S and 23S rRNA gene clone libraries yielded seven and six novel acidobacterial operational taxonomic units (OTUs) respectively. The majority of the OTUs were affiliated with subgroups 7 and 8. One OTU was affiliated with subgroup 6, and one OTU could not be assigned to any of the present acidobacterial subgroups. Fluorescence in situ hybridization distinguished two morphologically distinct, rod‐shaped cells of the acidobacterial subgroups 7 and 8. Although the ecophysiology of Acidobacteria from Lower Kane Cave will not be fully resolved until cultures are obtained, acidobacterial cells were always associated with the potentially chemolithoautotrophic epsilon‐ or gammaproteobacterial filaments, suggesting perhaps a lifestyle based on heterotrophy or chemoorganotrophy.

Foraging ability in the scorpionfly Panorpa vulgaris: individual differences and heritability - M. Missoweit; S. Engels; K. P. Sauer (Behavioral Ecology and Sociobiology, 2006)

Assessment of multiple paternity in single litters from three species of carcharhinid sharks in Hawaii - Toby S. Daly-Engel; R. Dean Grubbs; Kim N. Holland; Robert J. Toonen; Brian W. Bowen (Environmental Biology of Fishes, 2006)

Comparison between recombinant baculo- and adenoviral-vectors as transfer system in cardiovascular cells - G. Grassi; H. Köhn; B. Dapas; R. Farra; J. Platz; S. Engel; S. Cjsareck; R. Kandolf; C. Teutsch; R. Klima; G. Triolo; A. Kuhn (Archives of Virology, 2006)

EEG gamma-band activity in rapid serial visual presentation - Cornelia Kranczioch; Stefan Debener; Christoph S. Herrmann; Andreas K. Engel (Experimental Brain Research, 2006)

In vitro measurements of optical properties of porcine brain using a novel compact device - N. Yavari; J. S. Dam; J. Antonsson; K. Wårdell; S. Andersson-Engels (Medical & Biological Engineering & Computing, 2005)

Miltefosine (Impavido): the first oral treatment against leishmaniasis - H. Sindermann; S. L. Croft; K. R. Engel; W. Bommer; H. J. Eibl; C. Unger; J. Engel (Medical Microbiology and Immunology, 2004)

Response of total night‐time respiration to differences in total daily photosynthesis for leaves in a Quercus rubra L. canopy: implications for modelling canopy CO 2 exchange - David Whitehead; Kevin L. Griffin; Matthew H. Turnbull; David T. Tissue; Victor C. Engel; Kim J. Brown; William S.F. Schuster; Adrian S. Walcroft (Global Change Biology, 2004)
Measurements of photosynthesis and respiration were made on leaves in summer in a Quercus rubra L. canopy at approximately hourly intervals throughout 5 days and nights. Leaves were selected in the upper canopy in fully sunlit conditions (upper) and in the lower canopy (lower). In addition, leaves in the upper canopy were shaded (upper shaded) to decrease photosynthesis rates. The data were used to test the hypothesis that total night‐time respiration is dependent on total photosynthesis during the previous day and that the response is mediated through changes in storage in carbohydrate pools. Measurements were made on clear sunny days with similar solar irradiance and air temperature, except for the last day when temperature, especially at night, was lower than that for the previous days. Maximum rates of photosynthesis in the upper leaves (18.7 μmol m −2 s −1 ) were approximately four times higher than those in the lower leaves (4.3 μmol m −2 s −1 ) and maximum photosynthesis rates in the upper shaded leaves (8.0 μmol m −2 s −1 ) were about half those in the upper leaves. There was a strong linear relationship between total night‐time respiration and total photosynthesis during the previous day when rates of respiration were normalized to a fixed temperature of 20°C, removing the effects of temperature from this relationship. Measurements of specific leaf area, nitrogen and chlorophyll concentration and calculations of the maximum rate of carboxylation activity, V cmax , were not significantly different between upper and upper shaded leaves 5 days after the shading treatment was started. There were small, but significant decreases in the rate of apparent maximum electron transport at saturating irradiance, J max ( P> 0.05), and light use efficiency, ɛ ( P 2 exchange for the full growing season. Introducing respiration as a function of total photosynthesis on the previous day resulted in a decrease in growing season night‐time respiration by 23% compared with the value when respiration was held constant. This highlights the need for a process‐based approach linking respiration to photosynthesis when modelling long‐term carbon exchange in forest ecosystems.

Changes in tissue optical properties due to radio-frequency ablation of myocardium - J. Swartling; S. Pålsson; P. Platonov; S. B. Olsson; S. Andersson-Engels (Medical & Biological Engineering & Computing, 2003)

Traits of the invasive Centaurea maculosa and two native grasses: effect of N supply - P. S. Blicker; B. E. Olson; R. Engel (Plant and Soil, 2002)

Photosynthetic characteristics in canopies of Quercus rubra, Quercus prinus and Acer rubrum differ in response to soil water availability - Matthew H. Turnbull; David Whitehead; David T. Tissue; William S. Schuster; Kim J. Brown; Victor C. Engel; Kevin L. Griffin (Oecologia, 2002)

Conditioned place preference for cocaine is attenuated in mice over-expressing the 5-HT 3 receptor - Allan A.; Galindo R.; Chynoweth J.; Engel S.; Savage D. (Psychopharmacology, 2001)

Conservation Implications of a Newly Discovered Bee Species on Isla Robinson Crusoe, Chile - Gregory J. Anderson; Gabriel Bernardello; Michael S. Engel (Conservation Biology, 2001)

GHOST – A Novel Airborne Gas Chromatograph for In Situ Measurements of Long-Lived Tracers in the Lower Stratosphere: Method and Applications - Oliver Bujok; Viceith Tan; Erich Klein; Ralf Nopper; Reimar Bauer; Andreas Engel; Marie-Theres Gerhards; Armin Afchine; Daniel S. McKenna; Ulrich Schmidt; Frank G. Wienhold; Horst Fischer (Journal of Atmospheric Chemistry, 2001)

Validity of Prior Absorption of Serum Samples with Reiter's Spirochetes in Serological Diagnosis of Borrelia burgdorferi Infections - W. Engel; A. Vogt; S. R. Batsford (European Journal of Clinical Microbiology & Infectious Diseases, 2000)

Transcriptional analysis of the gene for glutamine synthetase II and two upstream genes in Streptomyces coelicolor A3(2) - N. Weißschuh; D. Fink; S. Vierling; M. J. Bibb; W. Wohlleben; A. Engels (Molecular Genetics and Genomics, 2000)

Method for Precision Nitrogen Management in Spring Wheat: II. Implementation - Dan S. Long; Richard E. Engel; Gregg R. Carlson (Precision Agriculture, 2000)

Method for Precision Nitrogen Management in Spring Wheat: I Fundamental Relationships - Richard E. Engel; Dan S. Long; Gregg R. Carlson; Corey Meirer (Precision Agriculture, 1999)

Combined analysis of field and model data: A case study of the phosphate dynamics in the German Bight in summer 1994 - Th. Pohlmann; Th. Raabe; R. Doerffer; S. Beddig; U. Brockmann; S. Dick; M. Engel; K. -J. Hesse; P. König; B. Mayer; A. Moll; D. Murphy; et al. (Ocean Dynamics, 1999)

5-HT 3 receptor over-expression enhances ethanol sensitivity in mice - S. R. Engel; A. M. Allan (Psychopharmacology, 1999)

Abstracts of papers presented at the 15th conference of the weed science society of Israel - H. Eizenberg; Z. Tanaami; R. Jacobsohn; A. Lalazar; M. Hayut; M. Sibony; A. Tal; B. Rubin; M. Sibony; T. Yossef; D. Plakhine; Y. Kleifeld; et al. (Phytoparasitica, 1999)

Caddisflies (Trichoptera: Hydropsychidae) Used for Evaluating Water Quality of Large European Rivers - S. C. Stuijfzand; S. Engels; E. van Ammelrooy; M. Jonker (Archives of Environmental Contamination and Toxicology, 1999)

5-HT 3 receptor over-expression decreases ethanol self administration in transgenic mice - S. R. Engel; C. R. Lyons; A. M. Allan (Psychopharmacology, 1998)